Kemampuan Pemilihan Saham dan Penetapan Waktu Pada Manajer investasi Reksa Dana Saham di Indonesia - Tariza Putri Ramayanti; Keti Purnamasari (Faculty of Economic and Business, 2018)
Selectivity and Market Timing Ability of Mutual Fund Investment Manajer in IndonesiaThere are two aspects to examining whether mutual fund managers perform well and enable high return from mutual funds; these are selectivity and market timing ability. The purpose of this paper is to examine selectivity and market timing ability of Indonesia Mutual Funds from January 2009 to December 2016 using monthly returns. Treynor & Mazuy and Henriksson & Merton models applied to a sample size of 33 mutual funds. Both models show that the investment managers of mutual funds in Indonesia have no selectivity ability. The result also found that 11 mutual funds have positive statiscally significant market timing coefficient using Treynor & Mazuy models and 10 mutual funds have positive statiscally significant market timing coefficient using Henriksson & Merton Models.DOI: 10.15408/ess.v8i1.6552